2020
DOI: 10.1097/ijg.0000000000001497
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity Focused Ultrasound Treatment in Moderate Glaucoma Patients: Results of a 2-Year Prospective Clinical Trial

Abstract: Precis: Ultrasound Cyclo Plasty (UCP) treatment using high-intensity focused ultrasound (HIFU) is an effective and safe therapy to reduce intraocular pressure (IOP) in moderate glaucoma patients as was measured during a 2-year follow-up period. Purpose: The purpose of this study was to evaluate the long-term safety and efficacy of the UCP procedure using HIFU in moderate glaucoma patients. Patients and Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 21 publications
7
22
0
Order By: Relevance
“…The mean number of medications was similar from baseline until the last follow up visit, and, again, these findings agreed with previous reports [19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean number of medications was similar from baseline until the last follow up visit, and, again, these findings agreed with previous reports [19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 91%
“…In our population, the mean ± SD baseline IOP was 24.3 ± 2.9 mmHg, and 24 months after, at the last follow up visit, the mean ± SD IOP was 15.9 ± 3.6 mmHg. Previous published literature has reported a lowering percentage ranging from 28% to 38% after 1 year [20,21], from 40% to 42% after 2 years [23][24][25], and of 33% at 3 years [26]. In particular, in our study, the IOP decrease was maximal at 1 to 3 months after the treatment and then tended to stabilize.…”
Section: Discussionsupporting
confidence: 62%
“…Ultrasound cycloplasty, a cyclodestructive procedure that reduces aqueous humor production by utilizing a ring probe to propagate focused ultrasound, defined as 21 MHz pulses given sequentially for 4, 6, or 8 s across the surface of the eye, has been shown to reduce IOP in patients with glaucoma without notable morbidity. 79 Interestingly, ultrasound cycloplasty appears to demonstrate greater IOP reduction in patients with higher preoperative IOP, suggesting it is particularly valuable for treating patients with advanced-stage glaucoma. In a separate 2-year prospective interventional noncomparative study evaluating ultrasound cycloplasty in 15 patients with moderate open-angle glaucoma, a stable and statistically significant reduction (p = 0.005) in IOP was observed at 2 years follow up without notable intraoperative or postoperative complications.…”
Section: Clinicalmentioning
confidence: 99%
“…This successful outcome was presumed to be the result of focal damage to the ciliary epithelium. Ultrasound cycloplasty, a cyclodestructive procedure that reduces aqueous humor production by utilizing a ring probe to propagate high‐intensity focused ultrasound, defined as 21 MHz pulses given sequentially for 4, 6, or 8 s across the surface of the eye, has been shown to reduce IOP in patients with glaucoma without notable morbidity 79 . Interestingly, ultrasound cycloplasty appears to demonstrate greater IOP reduction in patients with higher preoperative IOP, suggesting it is particularly valuable for treating patients with advanced‐stage glaucoma.…”
Section: Ultrasound As Therapymentioning
confidence: 99%
“…UCP procedure was registered in China in 2017. Studies have shown that this device utilizes high intensity focused ultrasound technology to cure glaucoma patients by partial coagulation necrosis of the ciliary body, with decent tolerance and curative effect [8][9][10][11][12]. Compared with the above surgical methods, the EyeOP1 treatment has the advantages of non-invasive, precise positioning, effectively reducing intraocular pressure, fewer complications and lower pain score [13][14][15].…”
Section: Introductionmentioning
confidence: 99%